Multi-mineral microwave dielectric ceramic material and preparation method thereof
By adding MgO and SnO2 to the CaMgSi2O6 ceramic system, using wollastonite and black talc ore as the main raw materials, and combining the two-stage ball milling process, coexisting CaMgSi2O6 and Mg2SiO4 ceramic materials were prepared, which solved the problem of high ceramic dielectric loss and stable temperature. The problems of poor performance and high sintering temperature have been solved, and the stability and performance of ceramic materials have been improved.
Patent Information
- Application Number
- CN202411490477.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing CaMgSi2O6 ceramic system has high dielectric loss, poor temperature stability and high sintering temperature, which limits its further application in the field of microwave communications.
By adding MgO and SnO2 as additives, using wollastonite and black talc ore as the main raw materials, combined with a two-stage ball milling process, a multi-mineral microwave dielectric ceramic material with CaMgSi2O6 and Mg2SiO4 coexisting was prepared.
The stability and temperature stability of ceramic materials have been greatly improved, the sintering temperature is reduced, and the low -agency constant is maintained, which is suitable for the field of microwave communication.
Smart Images

Figure CN119349987A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to ceramic materials and a preparation method thereof, in particular to a multi-mineral microwave dielectric ceramic material and a preparation method thereof. Background Art
[0002] Microwave dielectric materials play an important role in the development of global science and technology, and their application range is very wide, such as the Internet of Things, radio broadcast communications, global positioning systems and broadcast satellite television. The rapid development of modern communication technologies such as the Internet of Things, satellite broadcasting and intelligent transportation has driven the performance optimization and product diversification of microwave dielectric materials. Recent studies have shown that low-loss microwave dielectric ceramics can reduce the size of components such as filters, oscillators and antennas, and enhance the miniaturization and integration of microwave devices, making a huge breakthrough in microwave communication technology.
[0003] CaMgSi 2 O 6 Ceramic systems have low dielectric constants (ε r =7-8), suitable for millimeter wave communication, and can also be used as a substrate material for microwave integrated circuits. However, its relatively low quality factor, low temperature stability, and high sintering temperature have hindered the development of CaMgSi 2 O 6 The further application of ceramics in the fields of science and technology and commerce. Therefore, how to further reduce CaMgSi 2 O 6 The dielectric loss of the ceramic system effectively adjusts the τ of the ceramic material. f value, lowering its sintering temperature, and keeping the dielectric constant as low as possible have become key technical issues that need to be solved urgently. Summary of the invention
[0004] Purpose of the invention: In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a multi-mineral microwave dielectric ceramic material with good dielectric property stability and no impurities. Another purpose of the present invention is to provide a method for preparing a multi-mineral microwave dielectric ceramic material that is convenient and controllable and can reduce the sintering temperature.
[0005] Technical solution: The multi-mineral microwave dielectric ceramic material of the present invention is sintered by the following raw materials in parts by weight: 192-224 parts of black talc, 160-192 parts of wollastonite, 8-12 parts of MgO, 4-8 parts of SnO 2 , 2 to 4 parts of kaolin tailings.
[0006] Furthermore, the main phase of the multi-mineral microwave dielectric ceramic material is CaMgSi 2 O 6 , the secondary phase is Mg 2 SiO 4, of which the mass of the main phase accounts for 68-74% and the mass of the secondary phase accounts for 26-32%.
[0007] Furthermore, the relative dielectric constant of the multi-mineral microwave dielectric ceramic material is 9.12 to 10.52, the quality factor is 73473 to 84624 GHz, and the resonant frequency temperature coefficient is -7 to -12 ppm / °C.
[0008] The method for preparing the multi-mineral microwave dielectric ceramic material comprises the following steps:
[0009] Step S1, crushing and grinding black talc, wollastonite and kaolin tailings respectively, and sieving them to obtain black talc powder, wollastonite powder and kaolin tailings powder;
[0010] Step S2, weighing black talc powder and MgO powder according to proportion, and mixing by ball milling;
[0011] Step S3, adding wollastonite powder to the product obtained in step S2, and continuing ball milling;
[0012] Step S4, drying, calcining, heat preservation, and cooling with the furnace;
[0013] Step S5: Mix the powder obtained in step S4 and SnO 2 Powder and kaolin tailings powder are ball-milled and mixed evenly, and then dried;
[0014] Step S6, taking out the powder obtained in step S5, preparing a blank from the powder and then sintering it to obtain a multi-mineral microwave dielectric ceramic material.
[0015] Furthermore, in step S1, the particle size of the black talc, wollastonite and kaolin tailings after crushing, grinding and screening is less than 45 μm.
[0016] Furthermore, in step S2, the particle size of MgO is 1-5 μm, the ball milling is wet ball milling, the ball milling speed is 150-200 r / min, and the ball milling time is 3-5 hours. Wet ball milling makes the material easier to grind, improves the grinding efficiency, and improves the uniformity of the material.
[0017] Furthermore, in step S3, the ball milling is wet ball milling, the ball milling speed is 250-300 r / min, and the ball milling time is 16-24 h.
[0018] Furthermore, in step S4, the calcination temperature is 750-900°C, and the holding time is 1-3h. Preferably, the heating rate is 3°C / min. When the calcination temperature is lower than 750°C, the powder contains the raw material phase, and the impurity phase is likely to appear in the subsequent sintering process; when the calcination temperature is higher than 900°C, the powder particle size becomes larger, and the reaction activity becomes worse in the subsequent sintering process.
[0019] Furthermore, in step S5, the ball milling is wet ball milling, the ball milling speed is 200-250 r / min, and the ball milling time is 8-12 h; the SnO 2 The particle size of kaolin tailings powder is 5-20μm, and the particle size of kaolin tailings powder is less than 25μm.
[0020] Furthermore, in step S6, the sintering temperature is 1050-1150°C, and after sintering, the temperature is kept for 4-6 hours, and then the temperature is reduced to 500-600°C at a rate of 5-10°C / min, and then cooled with the furnace. Preferably, the heating rate is 3°C / min. When the sintering temperature is lower than 1050°C, the sintering power of the ceramic material is insufficient, the density is reduced, and the performance is reduced; when the sintering temperature is higher than 1150°C, the ceramic grains grow abnormally, and the grains are coated during the grain growth process, resulting in an increase in porosity, a decrease in density, and a decrease in performance.
[0021] Preparation principle: The present invention introduces MgO additive into black talc and wollastonite ore to make up for the problem of insufficient Mg in the mineral material composition. Since the composition of black talc ore is mostly Mg and Si oxides, the premixing of MgO and black talc can ensure Mg 2 SiO 4 It appears in the final product in the form of a secondary phase, thus ensuring that the main crystalline phase of the final ceramic product is (CaMgSi 2 O 6 +Mg 2 SiO 4 ), thereby significantly reducing the dielectric loss of the material, Sn 4+ (SnO 2 ) can partially replace CaMgSi 2 O 6 and Mg 2 SiO 4 Si 4+ , which adjusts the degree of distortion of the oxygen octahedron at the B site, thereby improving the resonant frequency temperature coefficient τ of the ceramic material f .
[0022] Beneficial effects: Compared with the prior art, the present invention has the following significant features:
[0023] 1. Select MgO and SnO 2 As an additive, the microwave dielectric properties of ceramic materials are improved, including increasing the quality factor and adjusting the temperature coefficient of the resonant frequency to near zero. Kaolin tailings powder is selected as a sintering aid to reduce the sintering temperature of ceramic materials without reducing the dielectric properties of ceramics.
[0024] 2. Using wollastonite and black talc as the main raw materials, CaMgSi 2 O 6 and Mg 2SiO 4 Coexistence of low-cost microwave dielectric ceramic materials;
[0025] 3. Through the two-stage ball milling process, the black talc and MgO are fully pre-mixed and then combined with wollastonite to prevent the appearance of impurity phase after the ceramic powder is calcined, thereby ensuring the stability of the dielectric properties of the ceramic material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the XRD spectrum of the multi-mineral microwave dielectric ceramic material prepared in Example 3 of the present invention.
[0027] Figure 2 This is a SEM image of the multi-mineral microwave dielectric ceramic material prepared in Example 3 of the present invention.
[0028] Figure 3 This is a SEM image of the multi-mineral microwave dielectric ceramic material prepared in Comparative Example 1 of the present invention.
[0029] Figure 4 This is the XRD spectrum of the multi-mineral microwave dielectric ceramic material prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0030] The materials, reagents, instruments, etc. used in the following examples, unless otherwise specified, can be obtained from commercial sources. The experimental methods without specific conditions in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The specific compositions of black talc ore powder, wollastonite ore, and kaolin tailings are shown in Table 1. The particle size of MgO is 1 to 5 μm.
[0031] Table 1 Composition of black talc powder, wollastonite ore and kaolin tailings
[0032] sample <![CDATA[SiO 2 ]]> CaO MgO <![CDATA[Fe 2 THE 3 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Na 2 The]]> Loss on ignition Black Talc 65.64 0.19 23.39 0.05 0.48 0.38 5.79 Wollastonite 49.81 37.67 1.12 0.29 0.26 0.11 10.74 Kaolin tailings 72.86 1.52 2.12 1.14 12.04 4.04 6.28
[0033] Example 1
[0034] A method for preparing a multi-mineral microwave dielectric ceramic material comprises the following steps:
[0035] Step S1, crushing, grinding and sieving black talc, wollastonite and kaolin tailings respectively, so that the average particle size of black talc and wollastonite powder is 40 μm, and the average particle size of kaolin tailings powder is 20 μm.
[0036] Step S2, weighing 19.2 g of black talc powder, 19.2 g of wollastonite powder, and 0.8 g of analytically pure MgO powder, pre-mixing the black talc powder and MgO powder by ball milling, and wet-milling them at a rotation speed of 150 r / min for 3 h.
[0037] Step S3, suspending the ball milling and taking out the ball mill jar, adding wollastonite powder into the ball mill jar, and continuing the ball milling at a rotation speed of 250 r / min for 16 hours.
[0038] Step S4, drying the product obtained in step S3, placing it in a muffle furnace for calcination at 750°C and keeping it warm for 1 hour, with a heating rate of 3°C / min, and cooling it with the furnace.
[0039] Step S5: weigh analytically pure SnO 2 0.5g powder, 0.3g kaolin tailings powder, the calcined powder and SnO 2 , kaolin tailings powder and wet ball milled at 200r / min for 8h, and then dried. 2 The average particle size of the kaolin tailings powder is 20 μm, and the average particle size of the kaolin tailings powder is 20 μm.
[0040] Step S6, take out the powder obtained in step S5, press the green body and place it in a high-temperature muffle furnace for sintering. The sintering temperature is 1050°C, the heating rate is 3°C / min, the holding time is 4h, and then the temperature is reduced to 500°C at a rate of 5°C / min, and then cooled in the furnace to obtain a multi-mineral microwave dielectric ceramic material.
[0041] Phase contents (by mass ratio) of the multi-mineral microwave dielectric ceramic material obtained in this example are: CaMgSi 2 O 6 68.0%, Mg 2 SiO 4 The relative dielectric constant of the multi-mineral microwave dielectric ceramic material obtained in this embodiment is 9.92, the quality factor is 79231 GHz, and the resonant frequency temperature coefficient is -12 ppm / °C.
[0042] Example 2
[0043] A method for preparing a multi-mineral microwave dielectric ceramic material comprises the following steps:
[0044] Step S1, crushing, grinding and sieving black talc, wollastonite and kaolin tailings respectively, so that the average particle size of black talc and wollastonite powder is 40 μm, and the average particle size of kaolin tailings powder is 20 μm.
[0045] Step S2, weighing 20.0 g of black talc powder, 18.4 g of wollastonite powder, and 1.0 g of analytically pure MgO powder, pre-mixing the black talc powder and MgO powder by ball milling, and wet-milling them at a rotation speed of 175 r / min for 4 h.
[0046] Step S3, suspending the ball milling and taking out the ball mill jar, adding wollastonite powder into the ball mill jar, and continuing the ball milling at a rotation speed of 275 r / min for 18 h.
[0047] Step S4, drying the product obtained in step S3, placing it in a muffle furnace for calcination at 800°C and keeping it warm for 2h, with a heating rate of 3°C / min, and cooling it with the furnace.
[0048] Step S5: weigh analytically pure SnO 2 0.4g powder, 0.2g kaolin tailings powder, the calcined powder and SnO 2 , kaolin tailings powder and wet ball milled at 225r / min for 9h, and then dried. 2 The average particle size of the ore is 5 μm, and the average particle size of the kaolin tailings powder is 20 μm.
[0049] Step S6, take out the powder obtained in step S5, press the green body and place it in a high-temperature muffle furnace for sintering, the sintering temperature is 1100°C, the heating rate is 3°C / min, the holding time is 5h, and then the temperature is reduced to 550°C at a rate of 8°C / min, and then cooled with the furnace to obtain a multi-mineral microwave dielectric ceramic material.
[0050] Phase contents (by mass ratio) of the multi-mineral microwave dielectric ceramic material obtained in this example are: CaMgSi 2 O 6 70.5%, Mg 2 SiO 4 The relative dielectric constant of the multi-mineral microwave dielectric ceramic material obtained in this embodiment is 9.52, the quality factor is 82156 GHz, and the resonant frequency temperature coefficient is -11 ppm / °C.
[0051] Example 3
[0052] A method for preparing a multi-mineral microwave dielectric ceramic material comprises the following steps:
[0053] Step S1, crushing, grinding and sieving black talc, wollastonite and kaolin tailings respectively, so that the average particle size of black talc and wollastonite powder is 40 μm, and the average particle size of kaolin tailings powder is 20 μm.
[0054] Step S2, weighing 20.8 g of black talc powder, 17.2 g of wollastonite powder, and 0.8 g of analytically pure MgO powder, pre-mixing the black talc powder and MgO powder by ball milling, and wet-milling them at a rotation speed of 200 r / min for 5 h.
[0055] Step S3, suspending the ball milling and taking out the ball mill jar, adding wollastonite powder into the ball mill jar, and continuing the ball milling at a rotation speed of 300 r / min for 20 hours.
[0056] Step S4, drying the product obtained in step S3, placing it in a muffle furnace for calcination at 850°C and keeping it warm for 3 hours, with a heating rate of 3°C / min, and cooling it with the furnace.
[0057] Step S5: weigh analytically pure SnO 2 0.8g powder, 0.4g kaolin tailings powder, the calcined powder and SnO 2 , kaolin tailings powder and wet ball milled at 250r / min for 10h, and then dried. 2 The average particle size of the ore is 15 μm, and the average particle size of the kaolin tailings powder is 20 μm.
[0058] Step S6, take out the powder obtained in step S5, press the green body and place it in a high-temperature muffle furnace for sintering. The sintering temperature is 1150°C, the heating rate is 3°C / min, the holding time is 6h, and then the temperature is reduced to 600°C at a rate of 10°C / min, and then cooled with the furnace to obtain a multi-mineral microwave dielectric ceramic material.
[0059] Phase contents (by mass ratio) of the multi-mineral microwave dielectric ceramic material obtained in this example are: CaMgSi 2 O 6 71.6%, Mg 2 SiO 4 The relative dielectric constant of the multi-mineral microwave dielectric ceramic material obtained in this embodiment is 9.12, the quality factor is 84624 GHz, and the resonant frequency temperature coefficient is -7 ppm / °C.
[0060] Example 4
[0061] A method for preparing a multi-mineral microwave dielectric ceramic material comprises the following steps:
[0062] Step S1, crushing, grinding and sieving black talc, wollastonite and kaolin tailings respectively, so that the average particle size of black talc and wollastonite powder is 40 μm, and the average particle size of kaolin tailings powder is 20 μm.
[0063] Step S2, weighing 21.6 g of black talc powder, 16.2 g of wollastonite powder, and 1.2 g of analytically pure MgO powder, pre-mixing the black talc powder and MgO powder by ball milling, and wet-milling them at a rotation speed of 175 r / min for 4 h.
[0064] Step S3, suspending the ball milling and taking out the ball mill jar, adding wollastonite powder into the ball mill jar, and continuing the ball milling at a rotation speed of 275 r / min for 22 h.
[0065] Step S4, drying the product obtained in step S3, placing it in a muffle furnace for calcination at 900°C and keeping it warm for 2h, with a heating rate of 3°C / min, and cooling it with the furnace.
[0066] Step S5: weigh analytically pure SnO 20.6g powder, 0.4g kaolin tailings powder, the calcined powder and SnO 2 , kaolin tailings powder and wet ball milled at 225 r / min for 11 h, and then dried. 2 The average particle size of the ore is 10 μm, and the average particle size of the kaolin tailings powder is 20 μm.
[0067] Step S6, take out the powder obtained in step S5, press the green body and place it in a high-temperature muffle furnace for sintering, the sintering temperature is 1100°C, the heating rate is 3°C / min, the holding time is 5h, and then the temperature is reduced to 550°C at a rate of 8°C / min, and then cooled with the furnace to obtain a multi-mineral microwave dielectric ceramic material.
[0068] Phase contents (by mass ratio) of the multi-mineral microwave dielectric ceramic material obtained in this example are: CaMgSi 2 O 6 72.9%, Mg 2 SiO 4 The relative dielectric constant of the multi-mineral microwave dielectric ceramic material obtained in this embodiment is 10.31, the quality factor is 78482 GHz, and the resonant frequency temperature coefficient is -9 ppm / °C.
[0069] Example 5
[0070] A method for preparing a multi-mineral microwave dielectric ceramic material comprises the following steps:
[0071] Step S1, crushing, grinding and sieving black talc, wollastonite and kaolin tailings respectively, so that the average particle size of black talc and wollastonite powder is 40 μm, and the average particle size of kaolin tailings powder is 20 μm.
[0072] Step S2, weighing 22.4 g of black talc powder, 16.0 g of wollastonite powder, and 1.0 g of analytically pure MgO powder, pre-mixing the black talc powder and MgO powder by ball milling, and wet-milling them at a rotation speed of 150 r / min for 3 h.
[0073] Step S3, suspending the ball milling and taking out the ball mill jar, adding wollastonite powder into the ball mill jar, and continuing the ball milling at a rotation speed of 250 r / min for 24 hours.
[0074] Step S4, drying the product obtained in step S3, placing it in a muffle furnace for calcination at 850°C and keeping it warm for 1 hour, with a heating rate of 3°C / min, and cooling it with the furnace.
[0075] Step S5: weigh analytically pure SnO 2 0.4g powder, 0.2g kaolin tailings powder, the calcined powder and SnO 2, kaolin tailings powder and wet ball milled at 200r / min for 12h and dried. 2 The average particle size of the ore is 10 μm, and the average particle size of the kaolin tailings powder is 20 μm.
[0076] Step S6, take out the powder obtained in step S5, press the green body and place it in a high-temperature muffle furnace for sintering. The sintering temperature is 1050°C, the heating rate is 3°C / min, the holding time is 4h, and then the temperature is reduced to 500°C at a rate of 5°C / min, and then cooled in the furnace to obtain a multi-mineral microwave dielectric ceramic material.
[0077] Phase contents (by mass ratio) of the multi-mineral microwave dielectric ceramic material obtained in this example are: CaMgSi 2 O 6 74.0%, Mg 2 SiO 4 The relative dielectric constant of the multi-mineral microwave dielectric ceramic material obtained in this embodiment is 10.52, the quality factor is 73473 GHz, and the resonant frequency temperature coefficient is -11 ppm / °C.
[0078] Comparative Example 1
[0079] The black talc, wollastonite and kaolin tailings are crushed and refined to make the particle size of black talc and wollastonite powder less than 45μm, and the particle size of kaolin tailings powder less than 25μm. Weigh 20.8g of black talc powder, 17.2g of wollastonite powder and 0.8g of analytical pure MgO powder. The black talc powder is wet-milled at a speed of 200r / min for 5h, the ball milling is suspended and the ball mill is taken out, and the wollastonite powder is added to the ball mill and the ball mill is continued at a speed of 300r / min for 20h. After ball milling, the dried powder is placed in a muffle furnace for calcination at 850℃ and kept warm for 3h. The calcined powder is wet-milled at a speed of 250r / min for 10h. After ball milling and drying, the powder compact is placed in a high-temperature muffle furnace for sintering at a sintering temperature of 1050°C for 6 hours, then cooled to 600°C at a rate of 10°C / min, and then cooled in the furnace to obtain a microwave dielectric ceramic material. The phase content of the ceramic material (by mass ratio) is: CaMgSi 2 O 6 72.5%, Mg 2 SiO 4 It accounts for 27.5%.
[0080] Comparative Example 2
[0081] The black talc, wollastonite and kaolin tailings were crushed and refined to make the particle size of black talc and wollastonite powder less than 45μm, and the particle size of kaolin tailings powder less than 25μm. Weigh 20.8g of black talc powder, 17.2g of wollastonite powder and 0.8g of analytical pure MgO powder, pre-mix the black talc powder and MgO powder, wet-mill them at a speed of 200r / min for 5h, pause the ball milling and take out the ball mill, add wollastonite powder to the ball mill and continue ball milling at a speed of 300r / min for 20h. After ball milling, the dried powder was placed in a muffle furnace for calcination at 850℃ and kept warm for 3h. Weigh analytical pure SnO 2 0.8g powder, 0.4g kaolin tailings powder, the calcined powder and SnO 2 The powders were mixed and wet-milled at a speed of 250 r / min for 10 hours. After ball milling and drying, the powder compact was placed in a high-temperature muffle furnace for sintering at a sintering temperature of 1150°C for 6 hours, and then cooled to 600°C at a rate of 10°C / min, and then cooled with the furnace to obtain a microwave dielectric ceramic material. The phase content of the ceramic material (by mass ratio) is: CaMgSi 2 O 6 72.0%, Mg 2 SiO 4 Accounting for 28.0%.
[0082] Comparative Example 3
[0083] The black talc, wollastonite and kaolin tailings were crushed and refined to make the particle size of black talc and wollastonite powder less than 45μm, and the particle size of kaolin tailings powder less than 25μm. Weigh 20.8g of black talc powder, 17.2g of wollastonite powder and 0.8g of analytical pure MgO powder. The black talc powder was wet-milled at a speed of 200r / min for 5h, the ball milling was suspended and the ball mill was taken out, and wollastonite powder was added to the ball mill and continued to be ball milled at a speed of 300r / min for 20h. After ball milling, the dried powder was placed in a muffle furnace for calcination at 850℃ and kept warm for 3h. Weigh analytical pure SnO 2 0.8g powder, 0.4g kaolin tailing powder, the calcined powder and kaolin tailing powder are mixed and wet ball milled at a speed of 250r / min for 10h. After ball milling and drying, the powder compact is placed in a high-temperature muffle furnace for sintering at a sintering temperature of 1050℃ for 6h, and then cooled to 600℃ at a speed of 10℃ / min, and then cooled with the furnace to obtain a microwave dielectric ceramic material. The phase content of the ceramic material (by mass ratio): CaMgSi 2 O 6 72.2%, Mg 2 SiO 4 Accounting for 27.8%.
[0084] Comparative Example 4
[0085] The black talc, wollastonite and kaolin tailings were crushed and refined to make the particle size of black talc and wollastonite powder less than 45 μm, and the particle size of kaolin tailings powder less than 25 μm. Weigh 20.8 g of black talc powder, 17.2 g of wollastonite powder, 0.8 g of analytical pure MgO powder, and 0.8 g of analytical pure SnO 2 0.8g of powder and 0.4g of kaolin tailing powder are mixed by wet ball milling. First, the powder is ball milled at a speed of 200r / min for 5h, and then wet ball milled at a speed of 300r / min for 20h. After ball milling, the dried powder is placed in a muffle furnace for calcination at 850℃ and kept warm for 3h. The calcined powder is wet ball milled at a speed of 250r / min for 10h by wet ball milling. After ball milling and drying, the powder compact is placed in a high-temperature muffle furnace for sintering at a sintering temperature of 1150℃ and a holding time of 6h. Then, the temperature is reduced to 600℃ at a rate of 10℃ / min, and then cooled with the furnace to obtain a microwave dielectric ceramic material. The phase content of the ceramic material (by mass ratio): Ca 2 MgSi 2 O 7 41.6%, CaMgSi 2 O 6 30.1%, Mg 2 SiO 4 22.3%, CaSiO 3 2.7%, MgSiO 3 2.3%, SiO 2 It accounts for 1.0%.
[0086] Table 2 Performance of materials obtained in various embodiments and comparative examples
[0087]
[0088] Table 1 shows the microwave dielectric properties and sintering properties of multi-mineral ceramic materials under different formulations and process conditions in Examples 1 to 5. Among them, the ceramic sample prepared in Example 3 has the lowest relative dielectric constant, the highest quality factor, the resonant frequency temperature coefficient close to zero, and the lowest sintering temperature, which is the optimal example. Figure 1 As shown, the main phase is CaMgSi 2 O 6 , the secondary phase is Mg 2 SiO 4 Compared with Example 3, Comparative Example 1 prepared a 2 and ceramic samples of kaolin tailings, e.g. Figure 2 (Example 3) and Figure 3As shown in (Comparative Example 1), the ceramic material prepared in Comparative Example 1 has poor density and more pores, so the dielectric properties and sintering properties are poor. In Comparative Example 2, a ceramic sample without adding kaolin tailings was prepared, and the sintering performance was poor. In Comparative Example 3, a ceramic sample without adding MgO, SnO 2 The dielectric properties of the ceramic samples are poor overall. Comparative Example 4 does not use a two-stage ball milling process to fully pre-mix black talc and MgO before combining with wollastonite, resulting in a change in the phase composition, such as Figure 4 As shown, therefore, both the dielectric properties and the sintering properties are greatly reduced.
Claims
1. A multi-mineral microwave dielectric ceramic material, characterized in that: The invention is prepared by sintering the following raw materials in parts by weight: 192-224 parts of black talc, 160-192 parts of wollastonite, 8-12 parts of MgO, 4-8 parts of SnO2 and 2-4 parts of kaolin tailings.
2. The multi-mineral microwave dielectric ceramic material according to claim 1, characterized in that: Its master The physical phase is CaMgSi2O6, and the secondary physical phase is Mg2SiO4, wherein the mass of the main physical phase accounts for 68-74%, and the mass of the secondary physical phase accounts for 26-32%.
3. The multi-mineral microwave dielectric ceramic material according to claim 1, characterized in that: The relative dielectric constant of the multi-mineral microwave dielectric ceramic material is 9.12-10.52, the quality factor is 73473-84624 GHz, and the resonant frequency temperature coefficient is -7--12 ppm / °C.
4. A method for preparing a multi-mineral microwave dielectric ceramic material according to claim 1, characterized in that: The following steps are involved: Step S1, crushing and grinding black talc, wollastonite and kaolin tailings respectively, and sieving them to obtain black talc powder, wollastonite powder and kaolin tailings powder; Step S2, weighing black talc powder and MgO powder according to proportion, and mixing by ball milling; Step S3, adding wollastonite powder to the product obtained in step S2, and continuing ball milling; Step S4, drying, calcining, heat preservation, and cooling with the furnace; Step S5, mixing the powder obtained in step S4 and the SnO2 powder and kaolin tailings powder weighed in proportion by ball milling, and drying; Step S6, taking out the powder obtained in step S5, preparing a blank from the powder and then sintering it to obtain a multi-mineral microwave dielectric ceramic material.
5. The method for preparing a multi-mineral microwave dielectric ceramic material according to claim 4, characterized in that: In the step S1, the particle size of the black talc, wollastonite and kaolin tailings after crushing, grinding and screening is less than 45 μm.
6. The method for preparing a multi-mineral microwave dielectric ceramic material according to claim 4, characterized in that: In the step S2, the particle size of MgO is 1-5 μm, the ball milling is wet ball milling, the ball milling speed is 150-200 r / min, and the ball milling time is 3-5 h.
7. The method for preparing a multi-mineral microwave dielectric ceramic material according to claim 4, characterized in that: In the step S3, the ball milling is wet ball milling, the ball milling speed is 250-300 r / min, and the ball milling time is 16-24 h.
8. The method for preparing a multi-mineral microwave dielectric ceramic material according to claim 4, characterized in that: In the step S4, the calcination temperature is 750-900° C. and the holding time is 1-3 hours.
9. The method for preparing a multi-mineral microwave dielectric ceramic material according to claim 4, characterized in that: In the step S5, the ball milling is wet ball milling, the ball milling speed is 200-250 r / min, and the ball milling time is 8-12 h; the particle size of the SnO2 is 5-20 μm, and the particle size of the kaolin tailings powder is less than 25 μm.
10. The method for preparing a multi-mineral microwave dielectric ceramic material according to claim 4, characterized in that: In the step S6, the sintering temperature is 1050-1150°C, and after sintering, the temperature is kept for 4-6 hours, and then the temperature is reduced to 500-600°C at a rate of 5-10°C / min, and then cooled in the furnace.
Citation Information
Patent Citations
Microwave dielectric glass ceramic material and composition thereof
CN103193389A
Black talc mineral microwave dielectric ceramic material and preparation method thereof
CN115536377A
Near-zero-temperature-drift black talc mineral microwave dielectric ceramic material and preparation method thereof
CN116396067A
Manufacturing method for a display apparatus
KR1020240120702A
Low-temperature co-fired microwave dielectric ceramic material and preparation method thereof
US20170334785A1
Cited By
Low-loss CaMgSiO4-based microwave dielectric ceramic material and preparation method thereof
CN119797902A